Integrating Intra-Individual and Dyadic Factors in Examining Health Among Gay and Bisexual Men: A Narrative Review of Recent Literature. Issue 5 (2nd November 2020) - Robles, Gabriel; Bosco, Stephen C.; Dellucci, Trey V.; Starks, Tyrel J.
Abstract: Gay and bisexual men (GBM) experience disproportionate rates of mental health and other negative health outcomes. For GBM in relationships, contextualizing the myriad of negative outcomes as a dyadic process may provide insight into the mechanisms through which these adverse outcomes develop. The objective of this review is to examine the current state of the relationship science literature using a health framework, Relationship Process and Health . We conducted a search for articles using PubMed, PsycInfo, and Web of Science for empirical articles in English published in the past 15 years on GBM in a relationship, assessing attachment, and relationship functioning as predictors of health outcomes. We found 649 articles. After screening, 23 articles were identified and reviewed. Findings overwhelming identified HIV risk as the primary health outcome. Attachment was associated with relationship functioning and sexual risk behaviors. Relationship-specific components were largely used as predictors of sexual HIV transmission risk behaviors. Together, these studies suggest that relationship functioning is a prospective link between attachment and health-related outcomes. The literature has yet to examine empirically dyadic-level mechanisms that may explain the association between individual attachment and health outcomes aside from HIV risk, and needs more examination of other health disparities affecting GBM.